Kartini's Resistance in the Novel Habis Gelap Terbitlah Terang by Armijn Pane: Sociolinguistic Review - Yanti Melina Ambarita; Rosmawaty Harahap (Winaya Inspirasi Nusantara Foundation, 2025)
Raden Ajeng Kartini is a national hero who is known as a pioneer of women's emancipation. He is fa-mous for his work entitled Habis Gelap Terbitlah Terang. (RA) Kartini is a figure who can free women from legal constraints, which limit women from developing and progressing (being educated). Thanks to his efforts, now women can receive education freely. Since then, there has been gender equality be-tween men and women. This article aims to examine the novel Habis Gelap Terbitlah Terang using a sociolinguistic review. A sociolinguistic review is an approach that analyzes how language and writing style in novels reflect and influence the social and cultural context. So, in this article the author will analyze how novel writers use language to create meaning, express social and cultural identities, and reflect or influence social and cultural norms. The author completed this article using the literature study method. The library research method is a way of collecting and analyzing information from var-ious data sources in the library. This is a qualitative research method carried out by reading books, magazines and other data sources in the library.